Association of the 5-HTT gene-linked promoter region (5-HTTLPR) polymorphism with psychiatric disorders: review of psychopathology and pharmacotherapy - Kenna GA; Roder-Hanna N; Leggio L; Zywiak WH; Clifford J; Edwards S; Kenna JA; Shoaff J; Swift RM (Pharmacogenomics and Personalized Medicine, 2012)
George A Kenna1, Nick Roder-Hanna2, Lorenzo Leggio3, William H Zywiak4, James Clifford5, Steven Edwards3, John A Kenna6, Jessica Shoaff1, Robert M Swift11Center for Alcohol and Addiction Studies, Department of Psychiatry and Human Behavior, Brown University, Providence; 2College of Pharmacy, University of Rhode Island, Kingston; 3Center for Alcohol and Addiction Studies, Department of Community Health, Brown University, Providence; 4Butler Hospital, Providence, RI; 5Virginia Institute for Psychiatric and Behavior Genetics, Virginia Commonwealth University, Richmond, VA; 6College of Nursing, University of Rhode Island, Kingston, RI, USAAbstract: Serotonin (5-HT) regulates important biological and psychological processes including mood, and may be associated with the development of several psychiatric disorders. An association between psychopathology and genes that regulate 5-HT neurotransmission is a robust area of research. Identification of the genes responsible for the predisposition, development, and pharmacological response of various psychiatric disorders is crucial to the advancement of our understanding of their underlying neurobiology. This review highlights research investigating 5-HT transporter (5-HTTLPR) polymorphism, because studies investigating the impact of the 5-HTTLPR polymorphism have demonstrated significant associations with many psychiatric disorders. Decreased transcriptional activity of the S allele (“risk allele”) may be associated with a heightened amygdala response leading to anxiety-related personality traits, major depressive disorder, suicide attempts, and bipolar disorder. By contrast, increased transcriptional activity of the L allele is considered protective for depression but is also associated with completed suicide, nicotine dependence, and attention deficit hyperactivity disorder. For some disorders, such as post-traumatic stress disorder and major depressive disorder, the research suggests that treatment response may vary by allele (such as an enhanced response to serotonin specific reuptake inhibitors in patients with major depressive disorder and post-traumatic stress disorder with L alleles), and for alcohol dependence, the association and treatment for S or L alleles may vary with alcoholic subtype. While some studies suggest that 5-HTTLPR polymorphism can moderate the response to pharmacotherapy, the association between 5-HTTLPR alleles and therapeutic outcomes is inconsistent. The discovery of triallelic 5-HTTLPR alleles (LA/LG/S) may help to explain some of the conflicting results of many past association studies, while concurrently providing more meaningful data in the future. Studies assessing 5-HTTLPR as the solitary genetic factor contributing to the etiology of psychiatric disorders continue to face the challenges of statistically small effect sizes and limited replication.Keywords: 5-HTTLPR, SCC6A4, 5-HT, serotonin, genetics, alleles, triallele, psychiatric, polymorphisms, pharmacotherapy, psychopathology